Medical Supplies Vending Machine - Ng, Peck Huey; Chan, Eric Rudolphe Sai Hong; Abdul Rahman, Muhammad Najmulfirdaus; Zolkifli, Muhammad Faisal; Mohd Rosli, Nur Nabilah; Mahmud, Mohd Nazri (Journal of Electronic Voltage and Application, 2022)
In this paper, a novel development of a Medical Supplies Vending Machine is described for solving recent emerging problems. In the recent COVID-19 pandemic, demand for round-the-clock and urgent supply of medical supplies have surged to a point that is difficult to serve by the conventional supply chain, which largely relies on shops and pharmacy outlets to sell them during restricted opening hours only. As a result, many consumers are deprived of the supplies they need and succumb to their ailments. Therefore, a smart healthcare solution for these predicaments is urgently needed. A project to address this need is presented in this paper. The goal of the project is to design a vending machine system that can deliver medical supplies at anytime and anywhere with a secure cashless payment system, security access system and ability to send restocking alert message. The vending machine is developed by using an Arduino Mega and a NodeMCU ESP8266 Wi-Fi module as the microcontrollers. The hardware components include I2C serial LCD display, RC522 RFID module, push buttons, LEDs, resistors, 360° servo motors, metal springs, IR sensors and buzzer while the software required are Arduino IDE, Telegram and ME-QR website. Testing of the prototypes reveal that the system fulfills its intended functionalities including cashless payment, security access, ability to select multi-items for a single payment and also ability to send restocking alert message. However, there are limitations such as the feature of purchasing limit could not be implemented as Arduino Mega has only one processor. Nevertheless, this paper also suggests some areas of improvement on the functionalities for future development.